Применение консолидированного маркетинга для решения проблем сбыта продукции предприятий сельскохозяйственного машиностроения Украины - Михайлова, Л. И.; Нехай, Виктория Васильевна; Нехай, Вікторія Василівна; Nekhai, Viktoriia (My University, 2017)
RU: В статье указано на несовершенство в организации маркетинга производственных предприятий, обоснована целесообразность консолидации маркетинговых усилий, указано на принципы консолидированного маркетинга и их соответствие целям предприятия и отрасли. Предлагаемый вариант решения проблемы базируется на формировании сильной рыночной позиции предприятия, группы предприятий, товаров, использовании метода нейронной сети. EN: The article indicates the imperfection in the organization of the marketing of industrial enterprises, the expediency of consolidating marketing efforts, stated on the consolidated marketing principles and their consistency with the objectives of the enterprise and the industry. The proposed solution to the problem is based on the formation of a strong market position of the company, group of companies, products, using the method of the neural network.
Aapplication for consolidated marketing solve the problems product sales of agricultural engineering
Keywords: консолидация; маркетинг; рынок; сбыт; сельскохозяйственное машиностроение; нейронная сеть; consolidation; marketing; marke; sales; agricultural machinery; neural network